Science Process Skills and Attitudes toward Science of Lower Secondary Students of Merbau Island: A Preliminary Study on the Development of MaritimeBased Contextual Science Learning Media - Zulirfan, Zulirfan; Rahmad, Muhammad; Yennita, Yennita; Kurnia, Nina; Hadi, Muhammad Sofyan (Journal of Educational Sciences, 2018)
Science learning outcomes such as science process skills andattitudes toward science are still important issues in science education. Inthis study the researchers tried to get a picture of the students' learningoutcomes to get input on the learning process of science in the coastal area.As an initial study of the development of maritime-based contextual sciencelearning media, the purpose of this research is to know the extent of scienceprocess skill level, attitude toward science, and academic achievement ofstudents in coastal area. There were 114 students of the 8th grade of fourlower secondary schools in Merbau Island participated as respondents in thisstudy. Instruments used in data collection are science process skills tests andattitude toward science questionnaires for lower secondary school students.The results showed that 8th grade lower secondary school students inMerbau Island had high attitude toward science. On the contrary, the scienceprocess skills and academic achievement of their science are relatively low.